SEGMENTASI PASAR DAN PENETAPAN PASAR SASARAN PEMASARAN UDANG GALAH DESA PERING KECAMATAN BLAHBATUH KABUPATEN GIANYAR - MADE ANTARA; ANAK AGUNG OKA UTARI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
Conducting Large Prawn have very good prospect if supported by correctmarketing, in this case which is prawn conducting of the Pering village, BlahbatuhDistrict, Gianyar Regency. To increase the accuracy of marketing, done by marketsegmentation, which is grouping market become some categories -as according tocertain criteria’s.The purpose of these researches is to know market segmentation and targeting ofLarge Prawn marketing in Pering village. This Location Research is selected bypurposive sampling. Variable which has been analyzed in this researches aregeographical area variable, type of effort, prawn size, purchasing frequencies andpurchasing power. This research was held on May, 10th until June, 20th 2006, thosevariables have been analyzed with descriptive qualitative method.The prawn marketing mix in Pering village such as: (1). Product; prawn has 4 kind ofsize which are Jumbo prawn, King Prawn, Prawn, Shrimp. (2). Price; prawn’s price is notprofitable to the farmers. (3). Distribution; the prawn distribution into market through a verylong channel and complex. (4). Promotion; the prawn of Pering village is known by consumereven though by distributor that known from someone to the other one. The market of largeprawn marketing of Pering village divided into five segments according to variablethat has been analyzed. The pattern of targeting market selection from agribusiness inPering village is a selected specialization, which is to choose some market segmentsobjectively, which are each market segments are interesting and adequate, in this casethe restaurants or cafe with P (prawn) measure, purchasing frequencies less than 10times /month and purchasing power between 30 until 70 kg /month that exist in Kutaarea.To increase the accuracy of marketing, the farmers and all perpetrators of markethave to focus on the market activities and prawn product at the targeting market, butdo not overrule the other small market segments, because one day this small marketsegments will have potency to become wider. For the shake of marketing processfluency, it’s very important to pay attention on farmer’s price by cut market channeland actively involve the farmers in marketing.